(untitled) (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract Objective: To determine the incidence of fever after vaccination with the first dose of diphthe r ia -pe r tus s i s - te tanus(DPT) among exclusively breastfed and non-exclusively breastfed infants in Ibadan, Nigeria. Methods: A prospective study was conducted on a cohort of 710 infants who received first dose of DPT vaccine at the Immunisation Clinic of a tertiary health institution in Ibadan, between July and October 2011. Based on the feeding pattern in a 24-hour feeding recall by mothers, infants were classified into exclusive and nonexclusive breastfeeding groups. Each of the infant's mothers was provided with a digital thermometer and instructed on how to measure the temperature of her infant.The information about the incidence of fever was obtained by telephone on the third day after vaccination. Results: Only 682 completed the study. The overall rates of exclusive and non-exclusive breastfeeding were 48% and 52%, respectively. Compared with the infants who were non-exclusively breastfed, those who were breastfed exclusively had a risk for fever of 0.675 (95% CI, 0.558-0.817). The place of delivery and the highest level of education were confounders and effect modifiers of the association between breastfeeding and fever. Conclusions: These findings suggest that exclusive breastfeeding is associated with a decreased incidence of fever after immunisation. Keywords: Exclusive breastfeeding; Post-immunisation fever; Diphtheria-pertussis-tetanus vaccination; Nigeria